2021
DOI: 10.3389/fphar.2021.626614
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Vitamin D Supplement in Thyroidectomy Patients Based on Relative Decline of Parathyroid Hormone

Abstract: Background: In postthyroidectomy patients, hypocalcemia is the most common complication to prolong hospital stay and decrease patients’ satisfaction. Based on current evidence, it is recommended to supply vitamin D to patients with high risk of developing hypocalcemia. However, how to stratify the risk of patients remains challenging.Aim: We conducted a prospective study to evaluate the effect of vitamin D supplement (calcitriol) on high-risk hypocalcemia patients based on relative decline of parathyroid hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Only 4 of the 14 studies20 23 25 26 were multicentre, and the majority had no published protocol. All studies randomised patients into two arms (vitamin D supplementation vs control), although Hao et al 27 additionally divided patients into two cohorts by the relative decline of parathyroid hormone prior to randomisation; these were treated as two separate cohorts for analysis. The included studies focused on a wide range of patient conditions, including open heart surgery, cancer operations and both elective and emergency orthopaedic conditions requiring surgery (online supplemental table 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 4 of the 14 studies20 23 25 26 were multicentre, and the majority had no published protocol. All studies randomised patients into two arms (vitamin D supplementation vs control), although Hao et al 27 additionally divided patients into two cohorts by the relative decline of parathyroid hormone prior to randomisation; these were treated as two separate cohorts for analysis. The included studies focused on a wide range of patient conditions, including open heart surgery, cancer operations and both elective and emergency orthopaedic conditions requiring surgery (online supplemental table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of length of hospital stay were reported for eight studies 19 21 23 24 26–28 30. Of these, Hao et al 27 reported outcomes for two subgroups, defined by the relative decline of parathyroid hormone (≤70% and >70%), which were treated separately for analysis, giving a total of nine cohorts (n=1051 patients).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations